Iron-based alpha-Fe amorphous nanocrystalline soft magnetic alloy

By controlling the content of Co elements and reasonably adjusting the composition of iron-based/α-Fe amorphous nanocrystalline soft magnetic alloys, the challenges of existing iron-based/α-Fe nanocomposite thin strips in improving saturated magnetic induction strength and low coercive force are solved, and higher saturated magnetic induction strength and lower coercive force are achieved, reducing costs.

CN119673604APending Publication Date: 2025-03-21JIANGYIN KANGRUI MOLDING TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311208773.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing iron-based/α-Fe nanocomposite thin strips have challenges in improving saturated magnetic induction strength and low coercive force. The high Fe content leads to weak amorphous formation ability, difficult to control the preparation process, and high cost.

Method used

By controlling the content of Co elements, reasonably adjusting the alloy composition, an iron-based/α-Fe amorphous nanocrystalline soft magnetic alloy is designed, with the specific component being FeaCobXcCud, where a, b, c, and d are the percentage of atomic molecules, 70≤a≤80, 6≤b≤8, 0.7≤d≤1; X is at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and other elements, and is prepared by an induction melting furnace and a single-roll belt method. The stress elimination of the longitudinal magnetic field is applied during the annealing stage and then high-temperature crystallization annealing is performed.

Benefits of technology

It achieves a higher saturated magnetic induction strength under the conditions of low coercive force, improves the comprehensive magnetic and mechanical properties of the alloy, expands the crystallization heat treatment window, and reduces the cost of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673604A_ABST
    Figure CN119673604A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based / alpha-Fe amorphous nanocrystalline soft magnetic alloy, which is based on an iron-based amorphous strip mainly comprising Fe element, and contains Co element with atomic fraction of 6%-8%, Cu element with atomic fraction of 0.7%-1%, and the balance of trace elements which are at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and the like. And carrying out stress relief annealing on the strip with the assistance of a magnetic field, and then carrying out crystallization treatment. Different from a traditional method for regulating and controlling the magnetic performance of the alloy through precipitation of a large number of nanocrystals, the alloy only induces precipitation of a very small number of nanocrystals, and high saturation flux density and low coercive force can be obtained while the toughness of the strip is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic alloy materials, and in particular relates to an iron-based alpha-Fe amorphous nanocrystalline soft magnetic alloy. Background Art

[0002] Iron-based / α-Fe amorphous nanocrystalline soft magnetic alloys (generally the initial forming material is called iron-based nanocomposite thin strips) are expected to be promoted and applied in new energy, 5G communications, power electronics and other fields due to their superior properties such as high saturation magnetic induction intensity, low loss soft magnetic properties and high effective magnetic permeability, in order to meet the needs of modern electronic and electrical equipment to develop in the direction of high frequency, high efficiency, lightweight and energy saving. However, although amorphous strips can obtain higher saturation magnetic induction (1.67-1.8T), they are still not comparable to traditional silicon steel. Increasing the Fe content is an effective way to increase the saturation magnetic induction of the strip. To this end, researchers have carried out a series of studies such as Fe 83.3-84.3 Si4B8P 3-4 Cu 0.7 , Fe 85 B 13 Ni2、Fe 83.2 P8B2C6Cu 0.8 In fact, the increase of Fe content will inevitably lead to a decrease in the content of non-magnetic amorphous glass-forming elements, which in turn affects the amorphous glass-forming ability and overall mechanical and magnetic properties of the strip. Therefore, it is imperative to explore new ways to improve the comprehensive magnetic and mechanical properties of the strip by regulating the alloy composition and optimizing the preparation process.

[0003] At present, researchers have conducted a series of related studies and applied for a number of national invention patents for the optimization design of the comprehensive magnetic properties of Fe-based / α-Fe nanocomposite ribbons, including:

[0004] In the patent 201910975982.9, Guilin University of Electronic Technology published a crystallization-controllable iron-based nanocrystalline soft magnetic alloy and its preparation method. The chemical composition of the alloy includes Fe, Si, B, Cu and P. The specific content (atomic percentage) is: Fe = 84%, Si = 2%, B = 11%, Cu = 1%, P = 2%. After crystallization treatment, the saturation magnetic induction of the alloy can reach 1.57-1.85T. However, due to the high Fe content and the volatile P element in the alloy, its preparation process is difficult to control and the amorphous forming ability is weak.

[0005] The Ningbo Institute of Materials Technology and Engineering of the Chinese Academy of Sciences published a kind of iron-based nanocrystalline soft magnetic alloy and its preparation method in patent CN105448448A. The chemical composition of the alloy includes Fe, Cu, P and C, and the specific content (atomic percentage) is: Fe = 83.25%, Cu = 0.75%, P = 10%, C = 6%. The production process adopts vacuum melting of the master alloy, and then single-roller rapid cooling and spraying of the amorphous strip in Ar atmosphere. However, the annealing process needs to be carried out in a rapid heating furnace, and the saturation magnetic induction intensity of the obtained alloy strip is relatively low, with a maximum of 1.69T.

[0006] Shenzhen Dongda Innovation Technology Co., Ltd. published a nanocrystalline soft magnetic material and its preparation method in patent CN1392573A. The chemical composition of the alloy includes Fe, Ni, P, B, Cu and Nb, and the specific content (atomic percentage) is: Fe = 60-64%; Ni = 12-18%; P = 13-16%; B = 5-7%; Cu = 0-2%; Nb = 0-3%. The production process adopts ball milling, ball milling at different speeds for 30-80 hours, and then heated to any temperature between the crystallization temperature and 30°C above the crystallization temperature in an inert gas atmosphere and kept warm for 0.5-1 hour. The saturation magnetic induction intensity of the obtained alloy is not high, the iron loss is high, and the processing is also relatively complicated.

[0007] Southeast University published a patent CN 110093565 B, which is an iron-based nanocrystalline alloy with a wide crystallization window and controllable soft magnetic properties. Its molecular formula is: Fe a Co b Si c B d P x Cu y , wherein a, b, c, d, x, y are atomic percentages, 60≤a≤85, 10≤b≤15, 0≤c≤6, 5≤d≤10, 5≤x<8, 1.7≤y≤2.2, a+b+c+d+x+y=100, and 2.5≤x:y≤4.5; the alloy has a wide crystallization window, the crystallization temperature range is 165-182℃, the crystallization annealing temperature is 390-510℃, the crystallization annealing temperature range is 120℃, and the holding time is 10-90 minutes. The alloy has a saturation magnetic induction intensity Bs of 1.73-1.81T, a coercive force Hc of 4-18A / m, a high Co content, and a slightly insufficient maximum saturation magnetic induction intensity.

[0008] In summary, although the above research work has improved the soft magnetic properties of the iron-based / α-Fe nanocomposite ribbons to varying degrees, the heat treatment process has stringent requirements on the process, and the prepared target alloy cannot simultaneously achieve high saturation magnetic induction intensity and low coercivity. In addition, the alloy composition contains a large number of precious metal elements, resulting in a high cost of the alloy, and contains volatile elements such as P, which makes it difficult to accurately control the processing technology. Therefore, exploring new methods to improve the comprehensive magnetic properties of the strip is of great significance for the current research and application of iron-based soft magnetic alloy materials. Summary of the invention

[0009] In view of the above problems, the present invention proposes an iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy. By controlling the content of the Co element, a higher saturation magnetic induction intensity can be obtained while ensuring low coercive force, and a soft magnetic material with better performance can be obtained under the premise of reasonably controlling costs.

[0010] The present invention designs an iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy, wherein the soft magnetic alloy material is an iron-based amorphous strip material mainly composed of Fe elements, and is characterized in that the molecular composition of the soft magnetic alloy material satisfies Fe a Co b X c Cu d , where a, b, c, d are atomic molecular percentages (molar fractions), a+b+c+d=100, 70≤a≤80, 6≤b≤8, 0.7≤d≤1; X is at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and other elements, and its cumulative atomic molecular percentage c=100-abd. That is, the thin strip contains Co element with an atomic fraction ratio (molar fraction) not higher than 8% and Cu element with an atomic fraction ratio not higher than 1%, and the remaining trace elements are at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and other elements;

[0011] Furthermore, the molecular formula of the soft magnetic alloy material satisfies: Fe 70 8Si 12 C9Cu1.

[0012] Furthermore, the molecular formula of the soft magnetic alloy material satisfies: Fe 78.3 Co8B7C4S2Cu 0.7 .

[0013] Furthermore, the molecular formula of the soft magnetic alloy material satisfies: Fe 77.2 6B 10 C6 0.8 .

[0014] Furthermore, the molecular formula of the soft magnetic alloy material satisfies: Fe 75.7 Co 7.5B 10 C6 0.8 .

[0015] Furthermore, the purity of raw materials for preparing the soft magnetic alloy is greater than 99%.

[0016] Furthermore, the soft magnetic alloy material is an amorphous alloy strip prepared by a single-roll strip-spinning method using an induction melting furnace.

[0017] Furthermore, the soft magnetic alloy material exhibits good bending toughness and does not break after being bent 180 degrees. At the same time, the alloy has excellent comprehensive magnetic properties, with a saturation magnetic induction intensity of 1.78 to 1.85 T and a crystallization heat treatment window of 105 to 130°C, which is expanded by no less than 20°C.

[0018] Furthermore, when preparing the soft magnetic alloy, in the annealing stage, stress relief annealing by applying a longitudinal magnetic field is first performed, followed by high temperature crystallization annealing.

[0019] On the other hand, an electronic device uses any of the aforementioned iron-based / α-Fe amorphous nanocrystalline soft magnetic alloys, so that the electromagnetic performance of the electronic device, its corresponding application performance or cost performance can be improved.

[0020] On the other hand, an electronic device uses any of the aforementioned iron-based / α-Fe amorphous nanocrystalline soft magnetic alloys, so that the electromagnetic performance, corresponding application performance or cost performance of the electronic device can be improved.

[0021] On the other hand, an electrical device uses any of the aforementioned iron-based / α-Fe amorphous nanocrystalline soft magnetic alloys, so that the electromagnetic performance, corresponding application performance or cost performance of the electrical device can be improved.

[0022] The advantages and beneficial effects of the present invention are as follows: the minimum and maximum values ​​of the saturation magnetic induction intensity of the iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy designed by the present invention are improved under the traditional preparation process, from 1.73 to 1.81 T, which is relatively superior in the existing soft magnetic alloy materials, to 1.75 to 1.85 T, and the high-temperature magnetic properties are good (small changes). The alloy only induces a very small amount of nanocrystal precipitation, which ensures the toughness of the strip while obtaining high saturation magnetic induction intensity and low coercive force. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the XRD (x-ray diffraction) spectrum of amorphous strip prepared by smelting;

[0024] Figure 2It is the DSC-TG (differential scanning calorimetry-thermogravimetric analysis) curve of the amorphous ribbon. DETAILED DESCRIPTION

[0025] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0026] Example 1

[0027] The present invention proposes an iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy, wherein the soft magnetic alloy material is an iron-based amorphous strip material mainly composed of Fe elements, and the molecular composition of the material satisfies Fe. a Co b X c Cu d , where a, b, c, d are atomic molecular percentages (molar fractions), a+b+c+d=100, 70≤a≤80, 6≤b≤8, 0.7≤d≤1; X is at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and other elements, and its cumulative atomic molecular percentage c=100-abd. That is, the thin strip contains Co element with an atomic fraction ratio (molar fraction) not higher than 8% and Cu element with an atomic fraction ratio not higher than 1%, and the remaining trace elements are at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and other elements;

[0028] Preferably, the soft magnetic alloy material molecular formula composition satisfies: Fe 77.2 6B 10 C6 0.8 The saturation magnetic induction intensity Bs of the material can reach 1.85T, and the coercive force Hc can reach 8.54A / m (the maximum value of the process parameters changed in the experiment is 201.7A / m). The specific performance is also related to the preparation method and process parameters. This embodiment is prepared by a traditional method. For details, please refer to the literature in the background technology, such as the Chinese patent with announcement number CN 110093565 B.

[0029] Preferably, the purity of raw materials for preparing the soft magnetic alloy is greater than 99%.

[0030] Preferably, the soft magnetic alloy material is an amorphous alloy strip prepared by a single-roll strip-spinning method using an induction melting furnace.

[0031] Preferably, the soft magnetic alloy material exhibits good bending toughness and does not break after being bent 180 degrees. At the same time, the alloy has excellent comprehensive magnetic properties.

[0032] Preferably, when preparing the soft magnetic alloy, in the annealing stage, stress relief annealing by applying a longitudinal magnetic field is first performed, followed by high temperature crystallization annealing.

[0033] In order to facilitate performance comparison, the present invention selects a prior art comparative example for comparative analysis with the present embodiment. The comparative example has a high saturation magnetic induction iron-based amorphous soft magnetic alloy, and its molecular formula composition is: Fe 83.2 B 10 C6 0.8 The preparation method and the stress relief annealing and recrystallization treatment experiments are exactly the same as those in the embodiment. The alloy structure, thermal properties and magnetic properties testing methods are exactly the same as those described in the embodiment.

[0034] Attached Figure 1 The figure shows the XRD (x-ray diffraction) spectrum of the amorphous strip prepared by smelting, and the XRD is measured by a D8Advance polycrystalline X-ray diffractometer. As can be seen from the figure, the XRD spectrum of the embodiment and the comparative example both shows a diffuse diffuse scattering peak, and no obvious crystallization diffraction peak appears. This feature is a typical amorphous structure, but from the overall peak characteristics, it can be seen that the addition of a small amount of Co seems to weaken the amorphous forming ability of the alloy.

[0035] Attached Figure 2 The DSC-TG (differential scanning calorimetry-thermogravimetric analysis) curve of the amorphous strip prepared by smelting is shown, wherein the DSC curve is measured by a NETZSCH DSC 404C differential scanning calorimeter, and the measured heating rate is 0.67°C / s, and the heating rate of the TG curve test is 0.33°C / s. It can be seen from the DSC curve (a) that compared with the comparative example, the initial crystallization exothermic peak temperature (TX1) of the embodiment is slightly shifted to the left, and the initial crystallization exothermic peak temperature (TX2) of the second exothermic peak is shifted to the right. Therefore, a larger crystallization heat treatment window (△T=TX2-TX1) can be obtained. This △T is the optimal heat treatment temperature range for obtaining the nanocrystalline structure required for excellent soft magnetic alloys. In addition, the Curie temperature (TC) of the comparative example and the embodiment alloy can be clearly seen from the TG curve (b), and it is found that the Curie temperature (453°C) of the embodiment strip is significantly higher than that of the comparative example strip (327°C), indicating that the former has better high-temperature magnetic properties.

[0036] The experimental results show that the saturation magnetic flux density of the amorphous nanocrystalline soft magnetic alloy strip of this embodiment is 1.75-1.85T, and the coercive force is 8.54-26.39A / m; while the saturation magnetic flux density of the comparative strip is 1.71-1.79T, and the coercive force is 4.79-13.2A / m. For soft magnetic alloys, it is difficult to increase the saturation magnetic flux density, and the influence of the material coercive force can be overcome by a reverse magnetic field, or it can be lower than 10Oe (1Oe≈79.6A / m). The material of the present invention has achieved an increase in saturation magnetic flux density while ensuring a lower coercive force, thereby improving its comprehensive application performance. On the other hand, the crystallization heat treatment window of the material of this embodiment is 105-130℃, which is expanded by no less than 20℃, and the Curie temperature is significantly higher than that of the comparative strip, indicating that the former has better high-temperature magnetic properties.

[0037] Example 2

[0038] The difference from Example 1 is that the molecular formula of the soft magnetic alloy material satisfies: Fe 70 8Si 12 C9Cu1, the material's saturation magnetic induction intensity Bs can reach 1.78T, and its coercive force Hc can reach 5.3A / m.

[0039] Example 3

[0040] The difference from Example 1 is that the molecular formula of the soft magnetic alloy material satisfies: Fe 78.3 Co8B7C4S2Cu 0.7 The saturation magnetic induction intensity Bs of this material can reach 1.81T, and the coercive force Hc can reach 10.64A / m.

[0041] Example 4

[0042] The difference from Example 1 is that the molecular formula of the soft magnetic alloy material satisfies: Fe 75.7 Co 7.5 B 10 C6 0.8 The saturation magnetic induction intensity Bs of this material can reach 1.75T, and the coercive force Hc can reach 8.2A / m.

[0043] Example 5

[0044] An electronic device, such as an electromagnet, an electromagnet pole, an earphone, a motor rotor, a small transformer, a pulse transformer, a relay, a sensor, a mutual inductor, a magnetic amplifier, an electromagnetic clutch, a solenoid valve, a choke core, a magnetic shield, a microwave device, a radio frequency element, etc., wherein the electronic device uses the iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy described in any one of the above embodiments 1 to 4 and a combination thereof, so that the electromagnetic performance of the electronic device, its corresponding application performance or cost performance are improved.

[0045] Example 6

[0046] An electronic device, such as a power supply, a transformer, a motor, a radar, an antenna, an offshore platform, a submersible, an electromagnetic catapult, a suspension system, a magnetic resonance imaging (MRI) device, a magnetic navigator, etc., wherein the electronic device uses the iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy described in any one of the above embodiments 1 to 4 and a combination thereof, so that the electromagnetic performance of the electronic device, its corresponding application performance or cost performance are improved.

[0047] Example 7

[0048] An electrical device, such as an electromagnet, a transformer, a motor, a disconnector, a relay protector, a surge arrester, a power supply, a reactor, a circuit breaker, a mutual inductor, an air conditioner, a pump, etc., wherein the electrical device uses the iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy described in any one of the above embodiments 1 to 4 and a combination thereof, so that the electromagnetic performance of the electrical device, its corresponding application performance or cost performance can be improved.

[0049] Analysis of the constituent elements of soft magnetic alloy materials:

[0050] ① Ferromagnetic elements. Ferromagnetic elements are usually Fe, Co and Ni. Fe, as the main element of iron-based alloys, has a high Bs. The Bs of the alloy can be further improved by adding Co and Ni elements and utilizing the exchange coupling between magnetic elements. In addition, the addition of Co elements can increase the Curie temperature of the alloy matrix and improve its high-temperature magnetic properties, while the addition of Ni elements can effectively alleviate the brittle fracture of the alloy and improve the corrosion resistance of the alloy.

[0051] ② Amorphous crystal forming elements. Amorphous crystal forming elements mainly include non-metallic elements such as C, B, P, Si and metal elements with larger radius such as Zr, Mo, Hf, Mn, V, Cr. Good amorphous crystal forming ability, high thermal stability of residual amorphous matrix and wide crystallization heat treatment window are the prerequisites for achieving the corresponding microstructure of amorphous nanocrystalline alloys with excellent comprehensive magnetic properties and stability. However, these elements are all non-ferromagnetic elements, and some are even antiferromagnetic elements. Their addition will inevitably reduce the ferromagnetic element content of the system, and they are prone to exchange coupling or metal-metal hybridization with iron elements, resulting in a significant decrease in Bs; secondly, because the elements involved are heavy metals or easily oxidized elements, their addition greatly increases the design cost and preparation difficulty of the alloy. Therefore, how to select these elements is the key to achieving alloy microstructure and excellent magnetic properties.

[0052] ③Nanocrystal-forming elements. The nanocrystals in the amorphous matrix that are beneficial to the improvement of comprehensive magnetic properties are mainly α-Fe(Si), and their grain size is smaller than Lex (40nm), corresponding to the first crystallization peak of the DSC curve. Studies have found that the precipitation of uniformly distributed and fine α-Fe(Si) nanocrystals is closely related to Cu or Cu-P-rich clusters in the range of 2-5nm in the matrix, and they precipitate preferentially attached to these clusters. Considering the large positive mixing enthalpy of Cu with Fe (+13kJ / mol, very small solid solubility or basically insoluble in Fe) and the large negative mixing enthalpy with P (-17.5kJ / mol), it becomes a key element for nanocrystal nucleation. However, the addition of this element increases the structural heterogeneity of the alloy melt during rapid cooling, and the amorphous forming ability and thermal stability of the system are reduced. Different from the action mechanism of Cu element, the addition of Nb element mainly slows down atomic diffusion and prevents the growth of α-Fe(Si) grains, thereby effectively controlling the size of nano-grains and refining the nano-grains. It is also beneficial to reduce the magnetostriction coefficient, expand the crystallization annealing temperature zone, and improve the brittleness and process performance of the alloy. Therefore, the simultaneous addition of Cu and Nb has important regulatory significance for the thermal stability, heat treatment process and microstructure optimization of amorphous nanocrystalline alloys.

[0053] According to the above analysis, the basic principle of the present invention is: the soft magnetic alloy element Fe or a small amount of Ni or Co replaces part of Fe, which is the basic element constituting the soft magnetic alloy. Among them, Fe is the cheapest and has a high Bs; adding Ni to Fe can improve the anisotropy of the material, but it should not be added too much, otherwise Bs will drop too much, adding Co can further improve Bs and increase Hc at the same time, but the amount added generally does not exceed 30% of Fe; the addition of Cu can not only improve the magnetic properties, but also hinder the growth of α-Fe crystal nucleus; the addition of Si and B is easy to form an amorphous alloy, and its substitute elements C, P, etc. may reduce the Bs value. Taking into account the cost factors of precious metal elements and the preparation process factors (such as P is volatile), while ensuring the performance of the alloy, the precious metal elements are used as little as possible. Based on the above principles and the experimental results of the prior art, the present invention proposes a method of forming an iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy material, using as much cheap Fe as possible, strictly controlling the addition of Co and Cu, and through a certain process, the obtained soft magnetic alloy has the characteristics of high saturation magnetic induction intensity, low coercivity, a large crystallization heat treatment window range, high Curie temperature, and good high-temperature magnetic properties. In addition, unlike the traditional method of regulating the magnetic properties of the alloy by precipitating a large number of nanocrystals, the alloy only induces the precipitation of a very small amount of nanocrystals, which ensures the toughness of the strip while being conducive to obtaining high saturation magnetic induction intensity and low coercivity.

[0054] The above description is only a partial embodiment of an iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy of the present invention. In fact, there are countless combinations of components in the composition of the product material. Due to different preparation process parameters, similar or better performance can be obtained. These combinations should also be regarded as the scope of protection of the present invention and will not be listed here one by one.

Claims

1. An iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy, wherein the soft magnetic alloy material is an iron-based amorphous strip mainly composed of Fe elements, characterized in that: The molecular composition of the soft magnetic alloy material satisfies Fe a Co b X c Cu d , wherein a, b, c, d are percentages of atomic molecules, a+b+c+d=100, 70≤a≤80, 6≤b≤8, 0.7≤d≤1; X is at least one of oxygen, sulfur, phosphorus, carbon, silicon, and boron.

2. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The soft magnetic alloy material molecular formula composition satisfies: Fe 70 8Si 12 C9Cu1.

3. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The molecular formula of the soft magnetic alloy material satisfies: Fe 78.3 Co8B7C4S2Cu 0.7 .

4. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The molecular formula of the soft magnetic alloy material satisfies: Fe 77.2 6B 10 C6 0.8 .

5. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The soft magnetic alloy material molecular formula composition satisfies: Fe 75.7 Co 7.5 B 10 C6 0.8 .

6. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 5, characterized in that: The soft magnetic alloy material is an amorphous alloy strip prepared by a single-roller strip-spinning method using a smelting furnace, and the purity of the raw materials used to prepare the soft magnetic alloy is greater than 99%.

7. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 5, characterized in that: The soft magnetic alloy material does not break after being bent at 180 degrees, and its saturation magnetic induction intensity is 1.75-1.85T, and its crystallization heat treatment window is 105-130°C.

8. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 5, characterized in that: When preparing the soft magnetic alloy, in the annealing stage, stress relief annealing by applying a longitudinal magnetic field is first performed, followed by high-temperature crystallization annealing.

9. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to claim 6, characterized in that: When preparing the soft magnetic alloy, in the annealing stage, stress relief annealing by applying a longitudinal magnetic field is first performed, followed by high-temperature crystallization annealing.

10. The iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to claim 7, characterized in that: When preparing the soft magnetic alloy, in the annealing stage, stress relief annealing by applying a longitudinal magnetic field is first performed, followed by high-temperature crystallization annealing.

11. An electronic device, characterized in that: The electronic device uses the iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 10.

12. An electronic device, characterized in that: The electronic device uses the iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 10.

13. An electrical device, characterized in that: The electrical device uses the iron-based / α-Fe amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Iron-based nanocrystalline magnetically soft alloy and preparation method thereof

    CN105448448A

  • Iron-based nanocrystalline alloys with wide crystallization windows and controllable soft magnetic properties and their preparation methods

    CN110093565B

  • Crystallization controllable iron-based nanocrystalline soft magnetic alloy and preparation method thereof

    CN110541116A

  • Nano crystal soft magnetic material and its preparing method

    CN1392573A